(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article presents the authors’ insights concerning the problem of implicit meanings in its historic, cultural and linguistic aspects, as well as the needs of participants of communication in creating special conditions for interpretation and understanding of the message. The aim of the article is to introduce the notion of a communicative triad and its main constituents, such as “a proper addressee” and “a side participant’. Much attention is given to special means of creating informational insufficiency, i.e. erasing the connection between the significant and the signified (code mismatching), ambiguous pronoun reference, reference to the content of the shared experience. Of special interest are the cases where the targeted recipient of communication receives a semiotic complication of the utterance, as well as the metonymic transference based on the connection between what a speaker produces and the reality the proper addressee perceives. The following conclusion is drawn: all the described mechanisms are viewed as realization of a most essential property of human communication, i.e. its selective character which is achieved through various kinds of transformations of the reported utterance, so that it reaches its proper addressee in the form and size that would correspond to the communicative interests of the speaker.